2018
DOI: 10.1080/20477724.2018.1516417
|View full text |Cite
|
Sign up to set email alerts
|

The predictive and diagnostic accuracy of vascular endothelial growth factor and pentraxin-3 in severe dengue

Abstract: This study aimed to evaluate vascular endothelial growth factor (VEGF) and pentraxin 3 (PTX-3) as predictive and diagnostic markers in differentiating severe dengue from non-severe dengue. The study was conducted in Ampang Health Clinic, Ampang Hospital and Serdang Hospital. The plasma levels of VEGF and PTX-3 were compared between severe dengue and non-severe dengue by ELISA from the day of presentation until discharged. Multiple logistic regression was used to develop predictive and diagnostic models by inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…A total of 26 included studies conducted between 1994 and 2017 were published between 2008 and 2018 . However, two studies were related, leaving a total of 25 studies of different settings .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 26 included studies conducted between 1994 and 2017 were published between 2008 and 2018 . However, two studies were related, leaving a total of 25 studies of different settings .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies clearly indicated that the analysis was prior to the diagnosis of SD: Low 2018 and Carrasco 2014 . Thus, these two studies could be considered as predictive models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations